2010
DOI: 10.1002/pon.1638
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment of siblings of children with cancer: a systematic review

Abstract: Research regarding siblings of children with cancer continues to be methodologically limited. The conclusions of qualitative and quantitative studies differ considerably. We propose a research agenda to propel this field forward including greater attention to alterations in normative development (as opposed to psychiatric conditions), development of more appropriate quantitative measures, examination of potential moderators of adaptation, and use of prospective longitudinal designs. Siblings of children with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
471
1
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(506 citation statements)
references
References 83 publications
20
471
1
14
Order By: Relevance
“…Statistical significance was defined as p < 0.05 for acceptance in the enter model. were between 19 and 23 years (mean = 24.0, SD = 3.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] at the time of investigation. The average time since loss was 6.3 years (range 2-9, SD = 2.3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical significance was defined as p < 0.05 for acceptance in the enter model. were between 19 and 23 years (mean = 24.0, SD = 3.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] at the time of investigation. The average time since loss was 6.3 years (range 2-9, SD = 2.3).…”
Section: Discussionmentioning
confidence: 99%
“…Siblings of children living with cancer have been observed to suffer characteristic patterns of psychological distress [21,22]. Studies have reported that the healthy siblings have more anxiety, depression and post-traumatic stress disorder, and a poorer quality of life than the normal population [22].…”
Section: Introductionmentioning
confidence: 99%
“…One cannot ignore all the therapeutic demands which lead the family to cut back on its social life [9]. This could result in the healthy siblings getting angry and turning against their sick sibling because the illness is conditioning their lives, and at the same time they may also experience guilt for having those feelings.…”
Section: Siblings Facing Illnessmentioning
confidence: 99%
“…Reported symptoms in siblings are: anxiety, negative emotional reactions, behavioural problems, poor social adjustment self-esteem, and post-traumatic stress symptoms (17)(18). However, Buchbinder et al [19] found that siblings of childhood cancer survivors were generally psychologically healthy.…”
Section: Introductionmentioning
confidence: 99%